2017
DOI: 10.18805/ijar.v0iof.9170
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Profile of Rajapalayam Dog Breed of Southern India

Abstract: Rajapalayam, an important dog breed of southern India which are maintained for guarding of farm houses and protection from wild animals. The aim of the present investigation is to study the karyology of this important dog population for cytological profiling. Metaphase plates were prepared after culturing of lymphocytes isolated from heparinized blood collected from animals of both the sexes. Giemsa banding, centromeric index, arm ratio and relative length were estimated through standard protocol. The cytogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Aspects of reproductive behavior of the dog, Canis familiaris, in general, have been studied rather extensively [21,22], although the Rajapalayam breed has been largely ignored. Raja et al [2] investigated the cytogenetic profile of this dog to throw some light on chromosomal abnormalities that would affect growth and fertility. Based on a morphometric analysis, it was indicated that the Rajapalayam dog population has been declining and the purity of the breed is at risk requiring conservation measures [1].…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of reproductive behavior of the dog, Canis familiaris, in general, have been studied rather extensively [21,22], although the Rajapalayam breed has been largely ignored. Raja et al [2] investigated the cytogenetic profile of this dog to throw some light on chromosomal abnormalities that would affect growth and fertility. Based on a morphometric analysis, it was indicated that the Rajapalayam dog population has been declining and the purity of the breed is at risk requiring conservation measures [1].…”
Section: Introductionmentioning
confidence: 99%
“…There exists great diversity of domestic animal breeds in India (Raja et al 2017). During the last two decades, there has been an increased thrust to recognize different breeds of animals leading to an increase in documented breeds and varieties.…”
mentioning
confidence: 99%